2000
DOI: 10.1159/000064842
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ET<sub>A</sub> and ET<sub>B</sub> Endothelin Receptor Subtype mRNA in Human Detrusor Cultured Smooth Muscle Cells

Abstract: The aim of this study was to determine the expression of the endothelin receptor subtype mRNAs in human detrusor cultured smooth muscle cells using reverse transcription-polymerase chain reaction (RT-PCR) and in situ hybridization (ISH). First strand cDNA was made from human detrusor cultured smooth muscle cells total RNA and used for PCR with primers designed to amplify fragments of the ETA and ETB endothelin receptor subtype cDNA sequences. Subcloned fragments of the ETA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…1,24). In the human bladder, Okamoto-Koizumi et al (30) demonstrated the presence of both ET A and ET B receptors and showed that ET A receptors mediate the mechanical response (29,30). However, the underlying mechanisms have not yet been examined even in terms of ionic channels in the plasma membrane.…”
mentioning
confidence: 99%
“…1,24). In the human bladder, Okamoto-Koizumi et al (30) demonstrated the presence of both ET A and ET B receptors and showed that ET A receptors mediate the mechanical response (29,30). However, the underlying mechanisms have not yet been examined even in terms of ionic channels in the plasma membrane.…”
mentioning
confidence: 99%